GLP-1R in diabetes mellitus: from basic discovery to therapeutics development - Li, Shujun; Huang, Nanqu; Wang, Mei; Huang, Wendi; Luo, Yong; Huang, Juan (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM), a metabolic disorder syndrome characterized by persistent hyperglycemia, has a complex pathogenesis. As the number of diabetic patients continues to grow globally, this disease has become a major and growing challenge in global public health. Glucagon-like peptide-1 receptor (GLP-1R) is a G protein-coupled receptor widely expressed on the surface of a wide range of cells in the human body, including pancreatic islet α, β and δ cells, as well as multiple tissues such as the intestines, stomach, lungs, heart, kidneys, and central nervous system. GLP-1R works through the combination of the endogenous ligand Glucagon-like peptide-1 (GLP-1) or exogenous agonists, which activate multiple intracellular signaling pathways that enhance insulin secretion, inhibit glucagon secretion, protect β-cells from apoptosis, delay gastric emptying and increase satiety. This makes GLP-1R a key target for diabetes treatment. This paper reviews the structural and functional characteristics of GLP-1R. Its role in glucose homeostasis and its application in diabetes treatment. It focuses on the mechanism of action of GLP-1R in pancreatic islet α-cells, β-cells and δ-cells, as well as its effects on the central nervous system and gastrointestinal tract. In addition, the article reviews the clinical progress of GLP-1R agonists, including their efficacy, safety and potential in the treatment of diabetes and related complications.